A Prospective Single-Center Clinical Trial Comparing Short-Term Outcomes of a Novel Non-Cavitating Handheld Lensectomy Device versus Phacoemulsification - Cannon NT; Scruggs K; Pantanelli SM (Clinical Ophthalmology, 2025)
Nathan T Cannon, Kathleen Scruggs, Seth M Pantanelli Department of Ophthalmology, Penn State College of Medicine, Hershey, PA, USACorrespondence: Seth M Pantanelli, Department of Ophthalmology, Penn State College of Medicine, Hershey, PA, USA, Tel +1 717 5315690, Email spantanelli@pennstatehealth.psu.eduPurpose: To compare the short-term outcomes of a non-cavitating lensectomy device (MICOR) to phacoemulsification.Patients and Methods: This was a two-arm prospective open-label clinical trial. Patients with visually significant cataracts at a single academic center between March and December 2023 were consecutively enrolled to undergo cataract surgery using either MICOR or phacoemulsification for nuclear fragmentation and lens removal. Adverse events (AE), lensectomy time, fluid use, and ultrasound energy use were assessed intraoperatively. Visual acuity, refraction, and AE were assessed on postoperative day one.Results: A total of 34 eyes of 23 patients were included in the MICOR arm and 50 eyes of 32 patients in the phacoemulsification arm. No difference (p = 0.727) in logMAR best corrected distance visual acuity was observed postoperatively between MICOR (0.14 ± 0.25) and phacoemulsification (0.16 ± 0.33), nor was any difference observed in AE rates [3% versus 8%, respectively (p = 0.644)]. Lens removal time was faster with MICOR [209 vs 255 s (p = 0.003)], including for grade 2 cataracts [203 vs 237 s (p = 0.008)]. Irrigation volume was less for MICOR [33 vs 62 mL (p < 0.001)], including for grade 2 [34 vs 60 mL (p < 0.001)] and 3 cataracts [36 vs 60 mL (p = 0.004)]. Mean cumulative dissipated energy for phacoemulsification was 8.7.Conclusion: Compared to phacoemulsification, MICOR has similar visual outcomes and adverse event rates while requiring less time, irrigation fluid, and ultrasound energy, suggesting MICOR is a viable alternative to phacoemulsification.Plain Language Summary: The MICOR nucleus fragmentation and lens removal device is a new non-ultrasound technology used in clear-cornea extracapsular cataract surgery. This study prospectively compares MICOR to the industry standard, phacoemulsification. Compared to phacoemulsification, MICOR results in equivalent short-term visual outcomes at similar adverse event rates. MICOR may be more time efficient, emits less energy, and uses less irrigation fluid compared to phacoemulsification, suggesting it is a viable alternative.Keywords: phacoemulsification, cataract extraction, biomedical technology